Reduction of N, N‐Dimethylcarboxamides to Aldehydes by Sodium Hydride–Iodide Composite. Issue 5 (6th May 2018) - Chan, Guo Hao; Ong, Derek Yiren; Yen, Zhihao; Chiba, Shunsuke
Abstract : A new and concise protocol for selective reduction of N, N ‐dimethylamides into aldehydes was established using sodium hydride (NaH) in the presence of sodium iodide (NaI) under mild reaction conditions. The present protocol with the NaH‐NaI composite allows for reduction of not only aromatic and heteroaromatic but also aliphatic N, N ‐dimethylamides with wide substituent compatibility. Retention of α ‐chirality in the reduction of α ‐enantioriched amides was accomplished. Use of sodium deuteride (NaD) offers a new step‐economical alternative to prepare deuterated aldehydes with high deuterium incorporation rate. The NaH‐NaI composite exhibits unique chemoselectivity for reduction of N, N ‐dimethylamides over ketones. Abstract :